Lung protection in patients undergoing pulmonary lobectomy: a new perspective for remote ischemic conditioning in surgery? - Prunier, Fabrice; Mirebeau-Prunier, Delphine (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
In 1993, Przyklenk et al. reported the fascinating finding that administering brief periods of non-lethal ischemia and reperfusion to the circumflex coronary artery reduces myocardial infarct size following a prolonged occlusion of the left anterior descending coronary artery, indicating that the protection produced by ischemic conditioning can potentially be transferred from one area of the heart to another, a phenomenon which has been named remote ischemic conditioning (RIC) (1). Further experimental studies then established that the heart could be protected against ischemia-reperfusion injury by instigating brief bursts of non-lethal ischemia and reperfusion as a conditioning stimulus to an organ or tissue remote from the heart, thus extending the concept of RIC to inter-organ conditioning. Once it had been demonstrated that RIC can be induced simply by applying a blood pressure cuff to a limb, the technique has quickly developed applications in a wide range of clinical scenarios of potential ischemia-reperfusion damage (2,3). A large number of cardiac surgery studies, for example, have applied RIC via three or four cycles of 5-min ischemia followed by 5-min reperfusion of the upper or lower limb, the majority reporting reduced post-operative cardiac biomarker release, with even amended clinical outcomes in long-term follow-up analyses of studies that had insufficient power to conclude on outcomes (4). Nevertheless, two large clinical trials recently failed to achieve improved clinical outcomes using RIC in the cardiac surgery setting (5,6). Among the several confounding factors that likely altered the RIC response in these studies, the use of propofol anesthesia proved puzzling, given that this substance was already known to abrogate the RIC-induced protection (7). Consequently, the potential of RIC to confer protection in patients undergoing cardiac surgery remains uncertain (8). Nevertheless, it still has great potential, due to its infarct-sparing effect in other clinical situations at risk of ischemia-reperfusion damage, such as acute myocardial infarction (9,10). Furthermore, RIC still has a major therapeutic value in protecting non-cardiac organs exposed to ischemia-reperfusion damage, such as the brain in strokes, liver and kidneys in transplantation, and even lungs in pulmonary surgery (11,12).